Synthesis, characterization and thermal behaviour of solid-state compounds of 4-methoxybenzoate with some bivalent transition metal ions - Rodrigues, E. C. [UNESP]; Siqueira, A. B. [UNESP]; Ionashiro, E. Y. [UNESP]; Bannach, G. [UNESP]; Ionashiro, Massao [UNESP] (Springer Nature, 2005)
Solid-state M-4-MeO-Bz compounds, where M stands for bivalent Mn, Co, Ni, Cu and Zn and 4-MeO-Bz is 4-methoxybenzoate, have been synthesized. Simultaneous thermogravimetry-differential thermal analysis (TG-DTA), differential scanning calorimetry (DSC), X-ray powder diffractometry, infrared spectroscopy, elemental analysis and complexometry were used to characterize and to study the thermal behaviour of these compounds. The results led to have information about the composition, dehydration, thermal stability and thermal decomposition of the isolated compounds. © 2005 Akadémiai Kiadó, Budapest.
Keywords: 4-methoxybenzoate; Bivalent transition metals; Thermal behaviour; Differential scanning calorimetry; Infrared spectroscopy; Ions; Synthesis (chemical); Thermodynamic stability; Thermogravimetric analysis; Transition metals; X ray powder diffraction; Metal ion salts; Thermal behavior; Organometallics